Current patterns of diet in community-dwelling older men and women: results from the Hertfordshire Cohort Study. - Robinson, S; Syddall, H; Jameson, K; Batelaan, S; Martin, H; Dennison, E; Cooper, C; Sayer, A (2009)
BACKGROUND: dietary patterns analysis takes account of the combined effects of foods and may be a more meaningful way of assessing dietary exposure than considering individual nutrients. Little is known about the dietary patterns of older adults in the UK. OBJECTIVE: to describe the dietary patterns of a population of community-dwelling older men and women and to examine factors associated with compliance with these patterns. SETTING AND PARTICIPANTS: 3,217 men and women aged 59-73 years who were participants in the Hertfordshire Cohort Study. METHODS: diet was assessed using an administered food frequency questionnaire; dietary patterns were identified using principal component analysis. RESULTS: two dietary patterns were identified. The first was characterised by high consumption of fruit, vegetables, oily fish and wholemeal cereals ('prudent' pattern); the second was characterised by high consumption of vegetables, processed and red meat, fish and puddings ('traditional' pattern). High 'prudent' diet scores were more common in women, in men and women in non-manual classes and in non-smokers (all P < 0.05), whilst high 'traditional' diet scores were more common in men, in men and women who had partners and were associated with higher alcohol consumption (all P < 0.05). CONCLUSIONS: we have described large variations in food consumption and nutrient intake amongst older adults that are likely to have implications for future health. The specific socio-demographic correlates of the dietary patterns provide insights into the contexts within which good and poor diets exist, and may help in the identification of opportunities for dietary intervention.